Palmatine Is a Plasmid-Mediated Quinolone Resistance (PMQR) Inhibitor That Restores the Activity of Ciprofloxacin Against QnrS and AAC(6ʹ)-Ib-cr-Producing Escherichia coli - Wang, Peng (Infect Drug Resist, 2020)
PURPOSE: The emergence of plasmid-mediated quinolone resistance (PMQR) is a global challenge in the treatment of clinical disease in both humans and animals and is exacerbated by the presence of different PMQR genes existing in the same bacterial strain. Here, we discovered that a natural isoquinoline alkaloid palmatine extracted from traditional Chinese medicinal plants effectively inhibited the activity of PMQR proteins QnrS and AAC(6′)-Ib-cr. METHODS: In total 120 clinical ciprofloxacin-resistant Escherichia coli (E. coli) were screened for the presence of qnrS and aac(6ʹ)-Ib-cr by PCR. Recombinant E. coli that produced QnrS or AAC(6ʹ)-Ib-cr proteins were constructed and the correct expression was confirmed by MALDI/TOF MS analysis and SDS-PAGE. A minimal inhibitory concentration (MICs) assay, growth curve assay and time-kill assay were conducted to evaluate the in vitro antibacterial activity of palmatine and the combination of palmatine and ciprofloxacin. Cytotoxicity assays and mouse thigh infection model were used to evaluate the in vivo synergies. Molecular docking, gyrase supercoiling assay and acetylation assay were used to clarify the mechanism of action. RESULTS: Palmatine effectively restored the activity of ciprofloxacin against qnrS and aac(6ʹ)-Ib-cr-positive E. coli strains in a synergistic manner in vitro. In addition, the combined therapy significantly reduced the bacterial burden in a mouse thigh infection model. Molecular docking revealed that palmatine bound at the functional large loop B of QnrS and Trp102Arg and Asp179Tyr in the binding pocket of AAC(6′)-Ib-cr. Furthermore, interaction analysis confirmed that palmatine reduced the gyrase protective effect of QnrS and the acetylation effect of AAC(6′)-Ib-cr. CONCLUSION: Our findings suggest that palmatine is a potential efficacious compound to restore PMQR-mediated ciprofloxacin resistance and warrants further preclinical evaluations.